La aplicación de los ritmos de carrera en el entrenamiento de la prueba de maratón para la mejora del rendimiento mediante la utilización de las reservas lipolíticas - Alonso Curiel, D. (Revista Internacional de Medicina y Sciencias de la Actividad y del deporte, 2003)
1.- Introduction and goals During the few last years, there has been an important evolution the performances in Marathon, both in the male female categories, but in a special way with regards to the women there are lot of facts that have led to this result like the diet, the material, the biomedicine control, etc. Otherwise, one fact that is sure is that today, one trains better and with a better relation within the needs of the competition.